Training audiotext on the scientific style of speech: preparation, organization, opportunities - Курилюк, Т.; Петренко, И.; Ливэй, Фань (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2017)
The аrticle is devoted to the issue of foreign students’ development of listening comprehension skills at the practical classes of Russian language. Noting that listening is one of the most difficult types of speech activity, authors stop at the issue of audiotext comprehension training that allows working on lexical, grammatical and phonetic skills simultaneously. In this case, listening is a training tool to get acquainted foreign students with new teaching material. It also acts as a means of developing skills in other types of speech activity, promotes the maintenance of the achieved level of speech proficiency and listening skills formation.When selecting and training the text for listening, the criteria to be guided (volume, new information, new vocabulary, linguistic difficulties and essential characteristics of the text) are given; qualitative and quantitative indicators of these factors are suggested in the article. Accordingly, authors identify the specific ways of converting the training written text into its variant adapted for listening.The current system of exercises aimed at overcoming separate difficulties of listening and developing its mechanisms, assumes semantic perception of the comprehension text in the conditions coming to the natural communication and communicative function fulfillment of listening comprehension training. It leads to the improvement of a semantic perception process and achievement of a certain level of understanding.